1991
DOI: 10.1111/j.1651-2227.1991.tb11755.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes of Peripheral Blood Lymphocytes during Acute Hepatitis A

Abstract: We investigated peripheral blood lymphocyte phenotypes of 74 patients at weekly intervals during the course of acute hepatitis A. In the second week after onset of jaundice, a significant elevation of total lymphocytes was observed (4,096 X 10(6) +/- 1,003 X 10(6)/l vs. controls 3,038 X 10(6) +/- 1,208 X 10(6)/l, p less than 0.005). However, no change in the relative percentage of B-cells (CD20+), T-cells (CD3+ or CD2+), or T-cell subpopulations (CD4+ helper cells and CD8+ suppressor cells) could be demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…One study suggested NK cells have the potential to control HAV infection, although this was carried out in HAV-infected fibroblasts rather than hepatocytes [75,76]. There is controversy over changes in NK cell frequency during Hepatitis A [77,78] but elevated NK cell NKG2A expression correlates with ALT, suggesting a possible role for NK cells in acute liver damage [78].…”
Section: Hepatitis Bmentioning
confidence: 99%
“…One study suggested NK cells have the potential to control HAV infection, although this was carried out in HAV-infected fibroblasts rather than hepatocytes [75,76]. There is controversy over changes in NK cell frequency during Hepatitis A [77,78] but elevated NK cell NKG2A expression correlates with ALT, suggesting a possible role for NK cells in acute liver damage [78].…”
Section: Hepatitis Bmentioning
confidence: 99%
“…Thus, there is a fairly normal nuclear : cytoplasmic ratio. 194 A substantial direct cytopathic effect of the virus on hepatocytes seems unlikely. It is most often thought to be malignancy associated, rather than directly premalignant, 170 although this concept has now been questioned in some cases.…”
Section: Histopathology Of Hepatitis Amentioning
confidence: 99%